Assessment of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio and platelet count as predictors of long-term outcome after R0 resection for colorectal cancer - Corrado Pedrazzani; Guido Mantovani; Eduardo Fernandes; Fabio Bagante; Gian Luca Salvagno; Niccolò Surci; Tommaso Campagnaro; Andrea Ruzzenente; Elisa Danese; Giuseppe Lippi; Alfredo Guglielmi (Scientific Reports, 2017)
Abstract Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and platelet count (PC) were shown to be prognostic in several solid malignancies. We analysed 603 R0 resected patients to assess whether NLR, PLR and PC correlate with other well-known prognostic factors and survival of patients with colorectal cancer (CRC). Receiver operating characteristic (ROC) curve analysis was performed to define cut-off values for high and low ratios of these indices. Univariate and multivariate analysis were used to determine the prognostic value of NLR, PLR and PC for overall and cancer-related survival. The distribution of NLR, PLR and PC in CRC patients was compared with 5270 healthy blood donors. The distribution of NLR, PLR and PC was significantly different between CRC patients and controls (all p < 0.05). A significant but heterogeneous association was found between the main CRC prognostic factors and high values of NLR, PLR and PC. Survival appeared to be worse in patients with high NLR with cancers in AJCC/UICC TNM Stages I-IV; nonetheless its prognostic value was not confirmed for cancer-related survival in multivariate analysis. After stratification of patients according to AJCC/UICC TNM stages, high PC value was significantly correlated with overall and cancer-related survival in TNM stage IV patients.